BRINGING POP-CULTURE INTO CLASSROOM: SPEAKING 3’S GOT TALENT ACTIVITY TO ENHANCE SPEAKING SKILL OF UNIVERSITY STUDENTS - Muhamad Hasbi (Ta'dib, 2016)
AbstractFollowing the widespread and growing popularity of English communication across the globe, the implementation of and the research on innovation in language teaching is mushrooming, especially in the teaching of English speaking. This study aims at measuring how far pop-culture themed classroom activity named Speaking 3’s Got Talent gives impacts for students speaking skill improvement at IAIN Salatiga, through an observation of a class in the English Department with a number of students of 30 undertaking Speaking 3 course in the odd-semester of the academic year of 2016/2017. Using a quantitative approach, this research utilizes questionnaire and direct observation for collecting data, and makes use of three methods of data analysis namely questionnaire scale-analysis, CEFR (The Common European Framework) speaking grid, and teacher’s made rubric for speaking for assessment which pinpoint three key measured variables namely students’ attitude toward the activity, teacher’s assessment toward students’ performance referring to both CEFR and teacher’s made rubric. This research finds that students had positive (excellent and very good) attitude towards the time, English, avatar, expertise and assessment variables of the activity and viewed that it is effective in downgrading their degree of stage fright; secondly, students obtain excellent and very good assessment in both the CEFR and teacher’s made rubric model. The three methods of measurements implied its affectivity in enhancing university students’ speaking skill and both student and teacher assessment recommend this activity to be applied in English classrooms.Keywords: speaking skill, pop-cultural activity, attitude, stage fright, assessment